Aspek Pidana dalam Undang-undang Jaminan Fidusia Menurut Hukum Pidana Islam (Analisis Putusan No. 509/Pid.Sus/2021/ PN.Jmb) - Febrian Batubara; Hermanto Harun; Ahmad Nazori; Samsul Hadi J; Retno Kusuma Wardani; M. Yusuf (NALAR FIQH: Jurnal Hukum Islam, 2023)
Islam as a religion that leads to salvation has discussed muamalah issues which are expected to be a guide for mankind. Consumer financing in installments with fiduciary agreements is currently the people's favorite. However, it causes many problems, namely criminal threats in the event of misappropriation of collateral. This study will explain the views of Islamic criminal law regarding fiduciary engagement in consumer financing and the legal sanctions regarding misappropriation of collateral in the context of Decision No. 509/Pid.Sus/2021/PN.Jmb. This type of study is normative legal research with a conceptual approach. Sources of data used were obtained from scientific journals, laws and regulations, fatwas of scholars, and books. The results of this study indicate that in this decision, the defendant was guilty of diverting fiduciary collateral items without the approval of the financing institution as the recipient of the guarantee and was sentenced to 1 year in prison and a fine of 50 million IDR and collateral items were handed over to the financing institution for execution. The analysis of Islamic criminal law in this case is that the defendant's actions are convincingly included in the “ghulul,” namely the crime act of diverting objects under his control even though the rights of other people are involved and are threatened with “ta’zir.”